Lions painting, Chauvet Cave (museum replica) - HTO (Wikimedia Commons, 2009)
Notice iconographique issue de Wikimedia Commons. Titre: Lions painting, Chauvet Cave (museum replica). Lions painted in the Chauvet Cave (Ardèche, France). This is a replica of the painting from the BrNo museum Anthropos (Czech Republic). The absence of the mane sometimes leads to these paintings being described as portraits of lionesses.
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; Wikimedia Commons; Peintures